"I'm Dealing With That": Illness Concerns of African American and White Cancer Patients While Undergoing Active Cancer Treatments. (July 2021) - Meghani, Salimah H.; Levoy, Kristin; Magan, Kristin Corey; Starr, Lauren T.; Yocavitch, Liana; Barg, Frances K.
Background: National oncology guidelines recommend early integration of palliative care for patients with cancer. However, drivers for this integration remain understudied. Understanding illness concerns at the time of cancer treatment may help facilitate integration earlier in the cancer illness trajectory. Objective: To describe cancer patients' concerns while undergoing cancer treatment, and determine if concerns differ among African Americans and Whites. Methods: A 1-time, semi-structured qualitative interview was conducted with a purposive subsample of cancer patients participating in a larger study of illness concerns. Eligible patients were undergoing cancer treatments and had self-reported moderate-to-severe pain in the last week. Analysis encompassed a qualitative descriptive approach with inductive thematic analysis. Results: Participants (16 African American, 16 White) had a median age of 53 and were predominantly females (72%) with stage III/IV cancer (53%). Illness concerns were largely consistent across participants and converged on 3 themes: symptom experience (pain, options to manage pain), cancer care delivery (communication, care coordination and care transitions), and practical concerns (access to community and health system resources, financial toxicity). Conclusions: The findings extend the scope of factors that could be utilized to integrate palliative care earlier in the cancer illness trajectory, moving beyond the symptoms- and prognosis-based triggers that typify current referrals to also consider diverse logistical concerns. Using this larger set of concerns aids anticipatory risk mitigation and planning (e.g. care transitions, financial toxicity), helps patients receive a larger complement of support services, and builds cancer patients' capacity toward a more patient-centered treatment and care experience.